The Review of Community Service Activities in Martial Arts: Ulasan Kegiatan Pengabdian Masyarakat di Bidang Olahraga Beladiri - Setyaningsih, Puji; Setiabudi, M. Agung (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
Community service activities are often carried out in the field of sports, including martial arts. This article aims to review community service activities carried out in the field of martial arts. The review was conducted through a search of scientific publications over the past 10 years. The search results were summarized and arranged according to year, theme or form of activity, type of martial art, and target partners. The summary results were recapitulated to obtain the number of activities according to categorization. The review results show an increase in the number of publications over the past 5 years and significant potential for similar activities. This review provides a basis for novelty in community service activities in the field of martial arts, so that aspects of activities that have not yet become a community service theme can be addressed.